2020
DOI: 10.1182/bloodadvances.2020001736
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic assay to assist clinical decisions for unclassified severe combined immune deficiency

Abstract: Key Points 3D organoid T-cell differentiation from a few hundred peripheral blood CD34+ cells was successfully achieved. 3D organoid T-cell differentiation could help physicians distinguish intrinsic from extrinsic defects underlying a clinical SCID phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 9 publications
(8 reference statements)
3
40
0
Order By: Relevance
“…We reported a similar loss of DP cells over time when co-culturing induced pluripotent stem cell-derived CD34 1 cells from patients with RAG-null mutations with OP9-DLL4 cells, concurrent with an accumulation of single-strand DNA breaks and impaired cell survival. 17 A similar mechanism may account for the lack of DP cells in patients with SCID and Omenn syndrome observed by Bifsha et al 16 at week 5. In vivo, such decline in the number of DP cells could contribute to the lack of circulating TCRab 1 CD3 1 cells in SCID patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We reported a similar loss of DP cells over time when co-culturing induced pluripotent stem cell-derived CD34 1 cells from patients with RAG-null mutations with OP9-DLL4 cells, concurrent with an accumulation of single-strand DNA breaks and impaired cell survival. 17 A similar mechanism may account for the lack of DP cells in patients with SCID and Omenn syndrome observed by Bifsha et al 16 at week 5. In vivo, such decline in the number of DP cells could contribute to the lack of circulating TCRab 1 CD3 1 cells in SCID patients.…”
Section: Discussionmentioning
confidence: 69%
“…In this article, we describe our observation of a similar block in T-cell development at the DP stage in patients with RAG deficiency, irrespective of the severity of their clinical and immunologic phenotype. In a companion article, Bifsha et al 16 reported a difference in the capacity of CD34 1 cells from patients with RAG deficiency manifesting as SCID or Omenn syndrome to generate DP cells. We reported a similar loss of DP cells over time when co-culturing induced pluripotent stem cell-derived CD34 1 cells from patients with RAG-null mutations with OP9-DLL4 cells, concurrent with an accumulation of single-strand DNA breaks and impaired cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…We have taken advantage of a monolayer co-culture system of patients’ bone marrow-derived CD34 + cells together with OP9/DL1 stromal cells and growth factors ( 49 ). Recently, two groups reported the use of artificial thymic organoids aggregating DLL4-expressing stromal cell lines (OP9/DLL4 and MS5-hDLL4) to facilitate the differentiation of CD34 + cells, isolated either from the patients’ bone marrow aspirate ( 52 ) or from their peripheral blood ( 131 ). Using these three-dimensional tools, they have shown that CD34 + cells of two cDGS patients, one with a TBX1 mutation and the other with a deletion at chromosome 22q11.2, had the potential to differentiate into CD3 + mature T-cells, in line with their disorder not affecting the HSC.…”
Section: Abnormalities Of Thymic Stromal Development and Functionmentioning
confidence: 99%
“…T cell lymphopaenia may mistakenly be ascribed to an undefined haematopoietic defect and a thymic aetiology only suspected after absent immune reconstitution post-HSCT. Novel tools are emerging to facilitate the distinction of primary haematopoietic defects from inborn errors of thymic stromal cells in patients presenting with genetically undefined severe T cell lymphopaenia [ 126 , 129 , 146 , 147 ]. These include the use of artificial thymic organoids that express DLL4 and can therefore support the differentiation of CD34 + haematopoietic stem cells (HSCs) into mature T cells [ 146 , 147 ].…”
Section: Diagnosis Of Inborn Errors Of Thymic Stromal Cell Developmenmentioning
confidence: 99%
“…Novel tools are emerging to facilitate the distinction of primary haematopoietic defects from inborn errors of thymic stromal cells in patients presenting with genetically undefined severe T cell lymphopaenia [ 126 , 129 , 146 , 147 ]. These include the use of artificial thymic organoids that express DLL4 and can therefore support the differentiation of CD34 + haematopoietic stem cells (HSCs) into mature T cells [ 146 , 147 ]. In principle, HSCs from patients with thymic stromal cell defects should be able to generate mature T cells, whereas the T cell differentiation capacity of HSCs derived from patients with haematopoietic defects is generally expected to be impaired, although there may be exceptions as has been seen for adenosine deaminase deficiency [ 146 , 147 ].…”
Section: Diagnosis Of Inborn Errors Of Thymic Stromal Cell Developmenmentioning
confidence: 99%